KEEFEKTIFAN MODEL PEMBELAJARAN CONTEKTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 30 MANDAU - Adrianis Adrianis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the low student social studies learning outcomes. this research was carried out at SDN 30 Mandau. The purpose of this study was to improve the learning outcomes of class III students at SD Negeri 30 Mandau. This study uses classroom action research. The study was conducted in 2 cycles, each through the stages of planning, implementation, observation, and reflection. The results showed that, in the initial data of students who were completed by 11 (45.8%) people while those who did not complete 13 (54.2%) people with incomplete categories. In the second cycle, students who completed completed increased to 18 (75%) while those who did not complete were 6 (25%) with complete categories. In the second cycle, the total number of students completed was 21 (87.5%) while the incomplete students were 3 (12.5%) people in the category of institutions. Based on these results it can be concluded that by applying the contextual teaching and learning (CTL) learning model can improve social studies learning outcomes of class III students of SDN 30 Mandau